2011
DOI: 10.1111/j.1551-2916.2011.04830.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Oxidation Resistance of Zirconium Carbide at 1500°C by Lanthanum Hexaboride Additions

Abstract: Addition of LaB6 is adopted to improve the oxidation resistance of ZrC at 1500°C. Mixed powder of ZrC‐25 vol% LaB6 is reactively hot pressed at 1900°C for 30 min under vacuum with an applied pressure of 25 MPa. The LaB6 reacts with ZrC to form ZrB2 and a layered La‐containing phase. ZrB2 improves the oxidation resistance of ZrC in static air. The La‐containing phase is beneficial to increasing the relative density of oxide scale during oxidation and in enhancing the oxide scale stability during exposure to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This relative density is higher than that (92.2%) of monolithic ZrC sintered with similar condition [3]. ZrC-SiC has much better oxidation resistance than monolithic ZrC [7]. Therefore, ZrC-SiC is a promising ceramic composite.…”
Section: Introductionmentioning
confidence: 61%
“…This relative density is higher than that (92.2%) of monolithic ZrC sintered with similar condition [3]. ZrC-SiC has much better oxidation resistance than monolithic ZrC [7]. Therefore, ZrC-SiC is a promising ceramic composite.…”
Section: Introductionmentioning
confidence: 61%
“…Some reported studies showed that when oxygen was dissolved in carbides, ZrC (1‐x) O x was first formed during the oxidation of ZrC . ZrO 2 was produced when dissolved oxygen in ZrC (1‐x) O x reached saturation, and ZrO 2 layer became thick and acted as a barrier to oxygen diffusion at low oxygen partial pressures.…”
Section: Resultsmentioning
confidence: 99%
“…Zirconium carbide (ZrC), as a member of ultra-high temperature ceramics (UHTCs), is an attractive coating material due to its relatively low density, high strength and modulus [10][11][12] . High efficiency supersonic atmospheric plasma spray (SAPS) has been successfully developed to deposit ceramic and metallic coatings [13] .…”
Section: Introductionmentioning
confidence: 99%